The influence of parental involvement on students’ math performance: a meta-analysis - Wang, Xueshen; Wei, Yun (Frontiers in Psychology, 2024)
IntroductionMany studies have confirmed that parental involvement can affect students’ academic performance, but few focus on the influence of parental involvement on students’ math performance by using meta-analysis. This meta-analysis investigates the influence of parental involvement on students’ math performance, along with their moderators.MethodsThrough searching Google Scholar, ERIC, EBSCO, Web of Science and ProQuest databases, a total of 25 empirical studies between 2015 to 2024 were published and 42 independent effect sizes were included. The estimation of effect size was obtained by converting the Fisher’s correlation coefficient and investigating the publication bias that affects meta-analysis studies. This study also conducted heterogeneity tests of the magnitudes grouped according to different moderators.Results and discussionThe results found parental involvement to had a significantly positive influence on the math performance of students. The analysis of moderating variables found participant, involvement type, grade level, geographical region, and evaluation content all had moderating effects. Finally, the research findings were discussed and suggestions were provided for how parents can be more effectively involved in students’ mathematical learning.